The Ethic Of Spiritual And Material Balance (Tawāzun) In Classical Islam As A Solution To The Value Crisis Of Modern Education - Mohammad Nu'man; Junaedi Junaedi (Jurnal Edusci, 2025)
Background, Modern education, despite its excellence in science and technology, faces an alarming value crisis, marked by moral degradation and widespread mental health issues among students. This crisis is rooted in an imbalanced paradigm: fragmentation due to the dichotomy of knowledge, a pragmatic-materialistic orientation, and the penetration of hedonistic values in the digital era. Aim, This research aims to offer the ethic of balance (tawāzun) from the intellectual treasury of classical Islam as a transformative solution. Method, Using a qualitative library research method. Results, this study analyzes the primary works of Muslim thinkers such as Al-Ghazali, Ibn Miskawaih, and Al-Mawardi. The analysis reveals that tawāzun is an ontological principle (personal, communal, cosmic) that rejects the world-hereafter dichotomy. Al-Ghazali emphasizes inner purification (tazkiyatun nafs). Ibn Miskawaih maps the psychological balance of the soul, and Al-Mawardi offers a socio-ethical framework. Conclusion. This concept is highly relevant for contemporary holistic education. Its implementation demands transformation on three levels: curriculum integration, innovation in affective-spiritual pedagogy, and the development of a balanced school culture. Implication. This reconstruction is expected to form the insān kāmil (the perfect human) who is intellectually intelligent, morally robust, and spiritually mature.